Using the ‘Buller phenomenon’ in experimental evolution studies of basidiomycetes - Duur K. Aanen (Fungal Genetics Reports, 2008)
In basidiomycetes, the monokaryons in a mating simultaneously exhibit two clearly distinct behaviors that can be considered as female and male roles, respectively: the acceptance of a nucleus, and the donation of a nucleus. However, since each monokaryon is a hermaphrodite, these two behaviors are difficult to distinguish. Here, I describe a simple method to select for the male role. A nucleus is serially passed through a non-evolving monokaryon, utilizing the ‘Buller phenomenon’. I describe some theoretical predictions that can be tested with this metho